Tiktok Shop: Penggunaan Metode EUCS (End User Computing Satifiction) terhadap Kepuasan Gen-Z - Mulyani, Eneng Sri; Lattu, Arny; Permana, M. Anton (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
As information technology and the internet develop, e-commerce platforms such as Tiktok shophave become an important part of life for Generation Z. Tiktok shopcombines social media with e-commerce, which allows creators and users to promote and sell products directly. via videos, live broadcasts and product catalogues. However, the popularity of Tiktok shophas also caused controversy because it is considered to be damaging market prices. After temporarily closing in October 2023, Tiktok shopreopened two months later in collaboration with PT. GoTo Gojek Tokopedia Tbk. The aim of this research is to analyze the level of satisfaction of Gen-Z consumers with Tiktok shopusing the (EUCS) method. The research results show that the variables of content, format and timeliness have a significant influence on user satisfaction, while the variables of accuracy and ease of use do not have a significant influence.